Inside asylum appeals : access, participation, and procedure in Europe - Gill, Nick (Law and migration., 2024)
"Appeals are a crucial part of Europe's asylum system, but remain poorly understood. Building on insights and perspectives from legal geography and socio-legal studies, this book shines a light on what takes place during asylum appeals and puts forward suggestions for improving their fairness and accessibility. Drawing on hundreds of ethnographic observations of appeal hearings, as well as research interviews, the authors paint a detailed picture of the limitations of refugee protection available through asylum appeals. Refugee law can appear dependable and reliable in policy documents and legal texts. However, this work offers the unique insight that, in reality, myriad social, political, psychological, linguistic, contextual and economic factors interfere with and frequently confound the protection that refugee law promises during its concrete enactment. Drawing on evidence from Austria, Belgium, France, Germany, Greece, Italy and the United Kingdom, the book equips readers with a clear sense of the fragility of legal protection for people forced to migrate to Europe. The book will appeal to scholars of migration studies, legal studies, legal geography and the social sciences generally, as well as practitioners in asylum law throughout Europe and beyond"--